2020
DOI: 10.1007/s15010-020-01469-6
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment modification after starting cART in people living with HIV: retrospective analysis of the German ClinSurv HIV Cohort 2005–2017

Abstract: Objective Combination antiretroviral therapy (cART) has markedly increased survival and quality of life in people living with HIV. With the advent of new treatment options, including single-tablet regimens, durability and efficacy of first-line cART regimens are evolving. Methods We analyzed data from the prospective multicenter German Clinical Surveillance of HIV Disease (ClinSurv) cohort of the Robert-Koch Institute. Kaplan–Meier and Cox proportional hazards models were run to examine the factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…These results correlate with published data from clinical trials and cohort studies. [ 12 , 16 ] This observation is of great interest because toxicity continues to be one of the main reasons for switching antiretrovirals, [ 26 ] although only 2.3% of patients in our cohort discontinued treatment due to mild or moderate issues. The main reasons for withdrawal were physicians’ decisions or clinical conditions other than HIV infection, which prevented continuation of DTG plus RPV.…”
Section: Discussionmentioning
confidence: 95%
“…These results correlate with published data from clinical trials and cohort studies. [ 12 , 16 ] This observation is of great interest because toxicity continues to be one of the main reasons for switching antiretrovirals, [ 26 ] although only 2.3% of patients in our cohort discontinued treatment due to mild or moderate issues. The main reasons for withdrawal were physicians’ decisions or clinical conditions other than HIV infection, which prevented continuation of DTG plus RPV.…”
Section: Discussionmentioning
confidence: 95%
“…First, they suggest that hypertension is common in people living with HIV, even in the era of contemporary ART, and indicates that people living with HIV, especially those receiving INSTIs or PIs, should have regular BP monitoring. This is important given that INSTIs are increasingly the preferred ART option [44–46]. The incidence of hypertension in this study was higher than in other predominantly Caucasian cohorts [15,35] but comparable to that in cohorts with significant CVD risk [47,48].…”
Section: Discussionmentioning
confidence: 53%
“…This finding suggests that although most INSTI-based regimens already have highly satisfactory efficacy and safety profiles [18], the regimen type remains an important differentiating factor for persistence among INSTI-based regimens. Previous studies from Europe and North America also found that STRs are associated with greater persistence than MTRs, but these studies usually included patients whose regimens contained disparate classes of third agents or no INSTIs [7][8][9][10]19]. Thus, this study including only patients initiating INSTI-based regimens allows for a more reliable evaluation of the effects of regimen type on persistence by excluding potential confounding effects from third agent class.…”
Section: Discussionmentioning
confidence: 99%
“…Discontinuation includes cessation of therapy altogether or switch to a different regimen. Previous studies from Europe and North America found that regimen types (single-tablet regimen [STR] versus multiple-tablet regimen [MTR]) [7][8][9][10], NRTI backbones [8,10], and third agents [9,11,12] can affect the persistence of initial regimens. However, the persistence of initial regimens has been rarely investigated in Asia.…”
Section: Introductionmentioning
confidence: 99%